Pollen grain viability of coconut accessions at low temperatures (Acta Scientiarum. Agronomy, 2014)
The aim of this study was to evaluate the storage potential of the pollen grains of Brazil Green Dwarf (BGD), Brazilian Tall (BRA) and Cameroon Red Dwarf (CRD) coconut accessions under different storage conditions. Representative plants of BGD, BRA and CRD accessions were selected from the Coconut Active Germplasm Bank of Embrapa Coastal Tablelands. The pollen grains were collected, placed in cryotubes and maintained under the following storage conditions: T1, refrigerator (-4°C); T2, freezer (-20°C); T3, ultra-freezer (- 80°C) and T4, liquid nitrogen (-196°C). The pollen grain viability was determined by staining with 1% acetic carmine and in vitro germination in a Lora culture medium at 30 and 60 days after the storage. Storage under refrigerator (-4°C), freezer (-80°C) and liquid nitrogen (-196°C) conditions promoted a better pollen grain viability of the Brazilian Tall coconut accession. Storage under freezer (-20°C) and liquid nitrogen (-196°C) conditions promoted a better pollen grain viability of the Cameroon Red Dwarf coconut accession. Storage under freezer (-20°C and-80°C) and liquid nitrogen (-196°C) conditions promoted a better pollen grain viability of the Brazil Green Dwarf coconut accession. The pollen grain viability of the Brazilian Tall coconut accession is stable after 30 and 60 days of storage.